5. ASSESSMENT OF SERUM VITAMIN D CONCENTRATION ON PATIENTS WITH END STAGE CHRONIC KIDNEY DISEASE WHO ARE ON PERITONEAL DIALYSIS AT THONG NHAT DONG NAI GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Introduction: Peritoneal dialysis is a kidney replacement treatment method that patients perform on their own as an outpatient. Vitamin D plays an important role in human health. Vitamin D deficiency is related to many organs dysfunction in the body such as cognition, immunity, cardiovascular and endocrine systems. Vitamin D deficiency worsens end-stage chronic kidney disease, affects patient survival, and causes a variety of bone disorders, mineral abnormalities, and vascular calcification.Objectives: This study aims to determine the concentration and prevalence of serum vitamin D deficiency, the relationship between serum vitamin D deficiency and some factors in peritoneal dialysis patients.Research methods: Cross-sectional descriptive study.Results: The average Vitamin D concentration in peritoneal dialysis patients was 20.29 ± 7.98 ng/ml, the lowest was 1.69 ng/ml and the highest was 47.17 ng/ml. The prevalence of vitamin D deficiency was 94.59%. Vitamin D and blood albumin levels are positively correlated (r = 0.48 and p < 0.001). There is a negative correlation between vitamin D concentration and blood PTH (r = - 0.25 and p < 0.05). There is no relationship between vitamin D concentration and age, BMI, peritoneal dialysis time, Hb, Calcium, phosphorus and blood protein.Conclusion: The prevalence of vitamin D deficiency in peritoneal dialysis patients is very high, most patients with vitamin D deficiency have muscle pain and cramps. Low serum albumin and high serum PTH concentration are associated with vitamin D deficiency.
Keywords: End-stage chronic kidney failure, peritoneal dialysis, vitamin D concentration.